2003
DOI: 10.4153/cmb-2003-053-x
|View full text |Cite
|
Sign up to set email alerts
|

On Density Conditions for Interpolation in the Ball

Abstract: Abstract. In this paper we study interpolating sequences for two related spaces of holomorphic functions in the unit ball of C n , n > 1. We first give density conditions for a sequence to be interpolating for the class A −∞ of holomorphic functions with polynomial growth. The sufficient condition is formally identical to the characterizing condition in dimension 1, whereas the necessary one goes along the lines of the results given by Li and Taylor for some spaces of entire functions. In the second part of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 7 publications
0
2
0
Order By: Relevance
“…The techniques used in the present paper seem not to be able to yield strict versions of Theorem 1.3. Lastly, it is expected that complementing sufficient conditions to Theorem 1.3 do not hold for domains ⊂ C d in dimension d > 1; see [13,24] for some possible generalizations of the results [40] to the unit ball. For the failure of sufficiency of the lattice density conditions [4,38] underlying Theorem 1.1 for coherent states in the Bargmann-Fock spaces on C d with d > 1, see, e.g., [25,31].…”
Section: Frames and Riesz Sequencesmentioning
confidence: 99%
“…The techniques used in the present paper seem not to be able to yield strict versions of Theorem 1.3. Lastly, it is expected that complementing sufficient conditions to Theorem 1.3 do not hold for domains ⊂ C d in dimension d > 1; see [13,24] for some possible generalizations of the results [40] to the unit ball. For the failure of sufficiency of the lattice density conditions [4,38] underlying Theorem 1.1 for coherent states in the Bargmann-Fock spaces on C d with d > 1, see, e.g., [25,31].…”
Section: Frames and Riesz Sequencesmentioning
confidence: 99%
“…Seip [13] gave a characterization of interpolating sequences of Bergman spaces on the unit disk. For the case of several variables, Marco and Massaneda [6] showed that Seip's condition for a sequence in the unit disk is sufficient to be of interpolating, however a complete generalization of Seip's characterization is not known yet. As for harmonic case, Choe and Yi [3] studied interpolations of harmonic Bergman spaces on the upper half-space of R n+1 and obtained a result similar to Amar.…”
mentioning
confidence: 99%